If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(7X + 5) = 11 + -1(x + -9) Reorder the terms: 7(5 + 7X) = 11 + -1(x + -9) (5 * 7 + 7X * 7) = 11 + -1(x + -9) (35 + 49X) = 11 + -1(x + -9) Reorder the terms: 35 + 49X = 11 + -1(-9 + x) 35 + 49X = 11 + (-9 * -1 + x * -1) 35 + 49X = 11 + (9 + -1x) Combine like terms: 11 + 9 = 20 35 + 49X = 20 + -1x Solving 35 + 49X = 20 + -1x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 49X = 20 + -35 + -1x Combine like terms: 35 + -35 = 0 0 + 49X = 20 + -35 + -1x 49X = 20 + -35 + -1x Combine like terms: 20 + -35 = -15 49X = -15 + -1x Divide each side by '49'. X = -0.306122449 + -0.02040816327x Simplifying X = -0.306122449 + -0.02040816327x
| w+3/4=52/3 | | 17(k+921)=714 | | 8x=289 | | 3x=580 | | -19(t+-17)=608 | | x/7(x-14y-5) | | 2x+3(-8/10)=-4 | | 2x-4y=-18 | | 8+2f+f=44 | | 9+3=711 | | 2/-7x+8 | | y+11=4/5(x+12) | | 4y-1=15 | | A=2*pi*r*h | | x^22-1=0 | | 6(j+3)-23=49 | | 4x^2-56x+112=0 | | -1=-5(t-78)+69 | | 2n-3=16 | | -6(d-97)=-12 | | 268-4x=41x+18 | | 3x^2(x^2-8)+6x+5=4x^4-6x(4x-1)+4 | | 97=5(c-79)-2 | | 5-7x=38-28x | | 3(10-2)=(3*10)-(3*2) | | -7x+8/2 | | 9x-7x=18 | | 7x+x-4x-7=5x | | 5(k-78)+-96=-51 | | 9x-7x=-30 | | 3.6-x=9 | | -7(q+56)=14 |